Implementation of the Teams Games Tournament (TGT) Learning Model in Teaching Nahwu (Arabic Grammar) Rules - Imro’atus Solikah; Anin Nurhayati; Choiruddin; Anis Zunaidah (Al-Wasil, 2026)
Learning the Nahwu is often considered difficult and boring by students because of its theoretical and requires in-depth understanding. This study aims to find out the implementation of the Teams Games Tournament (TGT) learning model as an alternative innovative learning strategy in improving students' understanding and motivation towards the Nahwu. The research method used a qualitative approach with a classroom action research design at Islamic Junior High School Sunan Gunung Jati, Tulungagung. This study used the CAR model from Kemmis and McTaggart which consists of four stages in each cycle, planning, acting, observing, and reflecting. The results of the study showed that (1) The implementation of the Teams Games Tournament learning model was done through the stages of presentation, learning in teams, games, tournaments, and team recognition. Student responses and activities during the implementation of TGT were very positive and the students' responses were motivated, happy, and helped. (2) The learning model also succeeded in transforming the students' perceptions of Nahwu from considered difficult and scary to challenging and fun. (3) The implementation of this learning had a significant positive impact on students' understanding of the Nahwu. This is indicated by the increase in the average student scores from pre-cycle, cycle I, and cycle II as well as the increase in students' abilities in understanding Nahwu in the aspects of conceptual understanding, tarkib analysis, and implementation of grammar in sentences. Overall, the TGT learning model has proven effective as an alternative learning strategy for Nahwu that can increase student motivation, activity, and understanding.